The impact of excreta disposal into Lagos lagoon on the lagoon ecosystem at Iddo discharge point in Apapa local government area of Lagos state Nigeria (2011)
This paper duels on the impacts of raw sewage on the lagoon ecosystems. The result of physiochemical and microbiological tests carried out on fish and sixteen water samples taken from Iddo in Apapa Local Government of Lagos State, Nigeria revealed pollution. E,coli, Proteus sp., Enterobacter sp., Aeromonas sp., Klebsiella sp., and Salmonella sp. Were isolated microorganisms identified in the samples. The quantity of Total Solid (802-2711ppm), Dissolved Solids (550-1990ppm), Biochemical Oxygen Demand (59-140ppm), Level of conductivity (120-500μS), colour (5- 10HU), and Nitrate (23-65ppm) found in the water samples also confirmed that the Lagoon environment is insalubrious. Finally, conclusion was drawn with the recommendation that sewage should be treated prior to discharge into any sphere of the environment.